Local Political Conflict and Pela Gandong Amidst the Religious Conflicts - HOEDODO, TONNY SB; SURJO, JOKO; QODIR, ZULY (Jurnal Studi Pemerintahan, 2013)
Pela Gandong which is believed by Ambonese forits propitiational value is in fact failed to preventhorizontal conflict that victimized a big number oflife and financial damages. However, Wayame villageis found to survive from those conflicts, and thecommunity of this village, comprising of Islam andChristian religious group, succeeds to maintain harmoniousrelation. The research aims at, first, describingthe perception of Wayamae village communityto Pela Gandong in the post-conflict period;second, analyzing the cultural competence of pelaGandong in conflict resolution in the era of technology.This research employed qualitative method,involving in-field data gathering based on officialreport, digging out information from the resourcepersons who were directly witnessing the conflict whenit occured and other references obtained throughForum Group Discussion (FGD). An analysis wasperformed to seek answer concerning on how thecommunity of Wayame village viewed Pela Gandongin post-conflict period, how it is – as a local wisdom– maintained in the middle of changing and howPela Gandong was revitalized. Research showed thatPela Gandong was maintained by involving all elementssuch as customary community and the government.Pela Gandong grew as the icon ofAmbonese society in settling conflicts by raisingawareness that they are Eastern people, collectivisticin nature, and place kinship into priority.KEYWORDS : Pela Gandong, Wayane village, Localwisdom, post-conflict.